Mandatory Dues Check-off Reviewed in Light of the US Supreme Court’s Decision in the Janus Case - Trudeau, Gilles (Relations industrielles / Industrial Relations, 2019)
The United States Supreme Court has recently ruled in the Janus Case that the agency shop (mandatory dues check-off) imposed by Illinois law on state employees violates the freedom of expression and association guaranteed by the US Constitution. This decision underscores the profoundly different status enjoyed by the Rand Formula in Canada, where it is considered an essential element of the nation-wide Wagner-type collective bargaining system. Not only is it permitted everywhere, legislation has made it mandatory, in one way or another, in a majority of Canadian jurisdictions, including Quebec. Furthermore, almost 30 years ago, the Supreme Court of Canada recognized that mandatory dues check-off did not interfere with the freedom of association or expression protected by the Canadian Charter of Rights and Freedoms.